Dual Energy Computed Tomography of Internal Carotid Artery: A Modified Dual-Energy Algorithm for Calcified Plaque Removal, Compared With Digital Subtraction Angiography - Qu, Hongying; Gao, Yongan; Li, Meiling; Zhai, Shuo; Zhang, Miao; Lu, Jie (Frontiers in Neurology, 2021)
Background: Computed tomography angiography (CTA) is a common tool for evaluation of ICA stenosis. However, blooming artifacts caused by calcified plaques might lead to overestimation of the stenosis grade. Furthermore, the intracranial ICA is more vulnerable to calcification than other ICA segments. Dual-energy computed tomography (DECT) with a modified three-material decomposition algorithm, may facilitate the removal of calcified plaques and thus increase diagnostic accuracy. Objectives: To assess the accuracy of the modified three-material decomposition algorithm for grading intracranial ICA stenosis after calcified plaque removal, with digital subtraction angiography (DSA) used as a reference standard. Materials and Methods: In total, 41 patients underwent DECT angiography and DSA. The three-material decomposition DECT algorithm for calcium removal was applied. We evaluated 64 instances of calcified stenosis using conventional CTA, the previous non-modified calcium removal DECT technique, the modified DECT algorithm, and DSA. The correlation coefficient (r2) between the results generated by the modified algorithm and DSA was also calculated. Results: The virtual noncalcium images (VNCa) produced by the previous non-modified calcium removal algorithm were named VNCa 1, and those produced by the modified algorithm were named VNCa 2. The assigned degree of stenosis of VNCa 1 (mean stenosis: 39.33 ± 19.76%) differed significantly from that of conventional CTA images (mean stenosis: 59.03 ± 25.96%; P = 0.001), DSA (13.19 ±17.12%, P < 0.001). VNCa 1 also significantly differed from VNCa 2 (mean stenosis: 15.35 ± 18.70%, P < 0.001). In addition, there was a significant difference between the degree of stenosis of VNCa 2 and conventional CTA images (P < 0.001). No significant differences were observed between VNCa 2 and DSA (P = 0.076). The correlation coefficient (r2) between the stenosis degree of the VNCa 2 and DSA images was 0.991. Conclusions: The proposed DECT with a modified three-material decomposition algorithm for calcium removal has high sensitivity for the detection of relevant stenoses, and its results were more strongly correlated with DSA than with those of conventional CTA or the previous non-modified algorithm. Further, it overcomes CTA’s previous problem of overestimating the degree of stenosis because of blooming artifacts caused by calcified plaques.